IMPLEMENTASI MODUL GLOBAL POSITIONING SYSTEM (GPS) PADA SISTEM TRACKING BUS RAPID TRANSIT (BRT) LAMPUNG MENUJU SMART TRANSPORTATION - Yetti Yuniati; Melvi Ulvan; Mardiyah Azzahra (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2017)
This research is to discuss about the tracking system at the Bus Rapid Transit (BRT) Trans Bandar Lampung using the Global Positioning System (GPS) module with the delivery position data bus via Short Message Service (SMS), which will be stored and processed with data base, so that we can know the bus position and display in web application of Geographic Information System (GIS). Testing of bus tracking system consists of data collection at every bus stop and the road Rajabasa - Sukaraja by installing a GPS module in the bus and get the fault tolerance of 51.0096 meters, average speed calculation of bus rate to determine the density of vehicle traffic obtained busiest streets of bus stop Ramayana to bus stop Simpur Center and from the bus stop Mall Kartini to bus stop Telkom (Bambu Kuning market)and bus arrival time in three time using time data and position coordinates buses have been obtained by the results of the longest time at 15:00 pm by total time from Rajabasa to Sukaraja and back again to Rajabasa of 86.2574 minutess, and testing display of bus stop in GIS web can be seen with the page  http://webgis.unila.ac.id, the web page containof  information about BRT like the bus stop location, the distance between bus stops, the arrival time of BRT at each bus stop vehicle density and the density of vehicle traffic routes Rajabasa - Sukaraja.  Keywords: Smart transportation, Bus Rapid Transit (BRT), Global Positioning System (GPS), Short Message Service (SMS), web Geoghgrapic Information System (GIS)